TYPES AND FUNCTIONS OF SWEAR WORDS USED IN AMERICAN SITCOM HOW I MET YOUR MOTHER SEASON ONE - Sarnika, Cucu (Journal of Language and Literature, 2018)
This research is an analysis of swear words used in American sitcom How I Met Your Mother season one. The aims of this research are to find out types of swear words and to describe the functions of swear words found in American sitcom How I Met Your Mother season one. This research uses qualitative method. The source data is taken from sitcom How I Met Your Mother season one. The writer uses Hughes’s theory to find out types of swear words and uses Anderssson and Thrudgill theory to find out its functions of swear words found in How I Met Your Mother season one. The result of this research shows six types of swear words and its functions from 44 data, there are: 1). Types of swear words related to sex (4 data) and it has two functions; expletive and humorous. 2). Types of swear words related to excrement (3 data) and it has two functions; expletive and humorous. 3). Types of swear words related to name of animal (3 data) and it has two function; expletive and humorous. 4). Types of swear words related to personal background (9 data) and it has two functions; abusive and humorous. 5). Types of swear words related to taboo or religion or oath (14 data) and it has four functions; expletive, abusive, humorous, and auxiliary. 6). Types of swear words related to mental illness (11 data) and it has four functions; expletive, abusive, humorous, and auxiliary.